Impact of Viral Marketing on Boosting Brand Awareness and Shaping Consumer Brand Preferences on Social Media - Zulfikar Fauzi (Politeknik Mardira Indonesia, 2024)
The rise in internet usage not only influenced Generation Z but also unexpectedly affected Generation X, as they turned to social media to find information about fashion. While the use of local fashion products in Indonesia was widespread, it wasn’t exclusive, presenting a challenge. The study sought to determine the relationship between Viral Marketing and Brand Awareness, as well as the connection between Brand Awareness and Brand Preferences among Generation X and Z consumers of local fashion. Viral marketing was analyzed through three aspects: informative, irritating, and entertaining. Brand awareness was divided into four categories: base of association, familiar-like, substance/commitment, and considered brand. Brand preference was evaluated based on three factors: price, quality, and packaging. The research used both descriptive and verification methods, targeting Generation X and Z local fashion consumers. A total of 170 questionnaires were distributed to each generation, and data were examined using path analysis. Hypotheses were tested using the t-test and the Whitney-Mann test to identify differences. The findings showed a strong connection between viral marketing and brand awareness, as well as between brand awareness and brand preference. Additionally, differences in behavior between Generation X and Generation Z were observed.